Mannose-modified erythrocyte membrane-encapsulated chitovanic nanoparticles as a DNA vaccine carrier against reticuloendothelial tissue hyperplasia virus - Feng, Yangyang; Tang, Feng; Li, Sheng; Wu, Daiyan; Liu, Qianqian; Li, Hangyu; Zhang, Xinnan; Liu, Ziwei; Zhang, Linzi; Feng, Haibo (Frontiers in Immunology, 2023)
The erythrocyte membranes used in nano-vaccines include high membrane stability, long circulation life, adaptability, and extremely good biocompatibility. Nanoparticles encapsulated by erythrocyte membranes are widely used as ideal drug delivery vehicles because of their high drug loading, long circulation time, and excellent biocompatibility. The mannose modification of delivery materials can help target mannose receptors (MRs) to deliver antigens to antigen-presenting cells (APCs). In this study, the antigen gene gp90 of avian reticuloendotheliosis virus (REV) was encapsulated with carboxymethyl chitosan (CS) to obtain CS-gp90 nanoparticles, which were coated with mannose-modified fowl erythrocyte membranes to yield CS-gp90@M-M nanoparticles. The physicochemical characterization and immune response of the CS-gp90@M-M nanoparticles were investigated in vitro and in vivo. CS-gp90@M-M nanoparticles were rapidly phagocytized in vitro by macrophages to induce the production of cytokines and nitric oxide. In vivo, CS-gp90@M-M nanoparticles increased cytokine levels, the CD4+/8+ ratio, REV-specific antibodies in the peripheral blood of chicks, and the mRNA levels of immune-related genes in the spleen and bursa of immunized chicks. CS-gp90@M-M nanoparticles could be targeted to lymphoid organs to prolong the retention time of the nanoparticles at the injection site and lymphatic organs, leading to a strong, sustained immune response. Moreover, the CS-gp90@M-M nano-vaccine showed a lasting immunoprotective effect and improved the body weight of chicks after the challenge. Overall, CS-gp90@M-M nanoparticles can be used in vaccine designs as an effective delivery carrier with immune response-enhancing effects.